Hubungan Antara Kecemasan Penyelesaian Skripsi dengan Mood Swing Pada Mahasiswa Semester Akhir - khoirunnisak; Kusnadi; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2024)
This study is entitled "The Relationship between Thesis Completion Anxiety and Mood Swings in Final Semester Students". The purpose of this study was to see if there was a relationship between thesis completion anxiety and mood swings in final semester students. This study uses a quantitative approach with a correlational research type, the population in this study were all final semester students of the 2021 Class of Islamic Guidance and Counseling Study Program totaling 138 people, so the sampling technique in this study used probability sampling (random sampling), which was 55 people. The data collection technique used a questionnaire with 19 statements, with the basis for decision making if rCount> rTable then the statement is declared valid. The data analysis technique used the Pearson product moment correlation test, with decision making if the Pearson product moment correlation value> rTable then there is a relationship between the two variables. The results of this study indicate that the Pearson correlation value (0.699)> rTable (0.266) the interpretation value is in the interval between 0.61 to 0.80. Based on the results of data hypothesis testing in the research conducted by the researcher, a relationship was found between the anxiety of completing the thesis and mood swings in final semester students. This is proven by the results of the Pearson correlation (r) value of 0.699, meaning that the relationship between the two variables is "strong" and the correlation is positive, meaning that the higher the Anxiety of Completing the Thesis, the higher the Mood Swing in Final Semester Students.